Retirement Luncheon for Chief Probation Officer Don Hogner - Watkins, Howard::::::::: (1988)
Head table of Ben Kelley, Fresno Municipal Court Judge Carl Evans, Superior Court Presiding Judge Mario Olmos, Fresno County Supervisor Judy Andreen, Fresno County Fresno County Economic Opportunities Commission Executive Director Joe Williams, and Jim Rowland